The Dimethyl Fumarate Experience: A Handy Drug With Broad Clinical Utility - Lorefice, Lorena; Casaglia, Elisa; Fronza, Marzia; Frau, Jessica; Fenu, Giuseppe; Pilotto, Silvy; Coghe, Giancarlo; Barracciu, Maria A.; Cocco, Eleonora (Frontiers in Neurology, 2021)
Abstract Objectives: The aim of this study was to characterise MS patients exposed to dimethyl fumarate (DMF) and to evaluate the predictors of therapeutic response. In addition, the study offers a picture of how DMF use has changed over the past few years in naive or switcher patients. Methods: In this observational monocentric study, we examined the prescription flow of DMF in MS patients categorised as naive or switchers (for safety/tolerability, ineffectiveness, and de-escalation strategy) from 2015 to 2019. Clinical and MRI data of DMF-treated patients were analysed and NEDA-3 status at 24 months was evaluated by the three assessment components (absence of clinical relapses; no EDSS progression; no radiological activity). Determinants of therapeutic response were also evaluated using regression analysis. Results: The sample included 595 MS patients exposed to DMF categorised as naïve (158; 26.5%) and switchers for reasons of safety/tolerability (198; 33.3%), inefficacy (175; 29.4%) and de-escalation strategy (64; 10.8%). A 15% increase of DMF use in naïve and horizontal shift groups was observed in the last 3 years of observation, while there was a drop, with prescription passed from ~ 20% to less than 5%, as an exit strategy from second line therapies. NEDA-3 status was calculated for 340 patients after 24 months of DMF treatment and achieved in 188 (55.3%) of these. Analysing the predictors of DMF response, we observed that lower annualised relapse rate (ARR) in 2 years pre-treatment (p=0.001) and being naïve patients (p=0.035) were associated with achievement of NEDA 3. Analogously, ARR in 2 years pre-treatment affected the NEDA-3 achievement at 24 months in patients of the de-escalation group (p=0.041), also indicating an effect related to latency in initiating DMF therapy (p=0.029). Conclusions. Our findings confirm DMF as a handy drug with broad clinical utility, with greater benefits for naive patients and horizontal switchers. Additionally, an increase in the flow of DMF prescriptions in these two groups of patients was also observed in our cohort.